Lateral condylar retrograde humeral nail for management of high-energy distal humeral fractures - Ahmed Fathy Sadek (Journal of Orthopaedic Surgery, 2019)
Purpose: Distal metaphyseo-diaphyseal humeral fractures are challenging particularly if open, comminuted, or associated with nerve injury. In cases of open distal complex metaphyseo-diaphyseal humeral fractures inamenable for traditional methods of fixation, retrograde intramedullary locked humeral nail with a new lateral condylar point of entry has been proposed. Methods: Two phases of study were conducted; phase I comprised computerized tomography evaluation of right humeri of 120 adult subjects, while phase II entailed prospective analysis of 18 patients who sustained firearm injuries resulting in open distal metaphyseo-diaphyseal humeral fractures associated with radial nerve injuries. All patients were surgically managed using lateral condylar retrograde humeral nailing with primary radial nerve exploration. Results: Distal sagittal medullary diameter of the humeral medulla was the narrowest in comparison to axial and coronal medullary diameters in phase II, which matched the results of phase I. The mean postoperative disability of the arm, shoulder, and hand score was 11.2 ± 6.4. Only five patients underwent subsequent successful tendon transfer. Conclusions: Lateral condylar retrograde humeral nail with early radial nerve exploration in cases of high-energy distal metaphyseo-diaphyseal humeral fractures yielded good results regarding union and spontaneous radial nerve recovery or later on reconstruction.